α-particle induced forward-backward electron emission from titanium nitride - Zhurenko, V.P.; Kononenko, S.I.; Kalantaryan, O.V.; Mysiura, I.N.; Avotin, S.S.; Rokhmanov, N.Ja. (Вопросы атомной науки и техники, 2018)
The electronic yields of forward and backward secondary ion-induced electron emission from titanium nitride
bombarded by α-particles from a radioisotope source were experimentally measured. It was shown that the ratio of
forward and backward electronic yields was approximately 1.79, which agrees well with the results obtained earlier
for other materials and fast light ions. It was found that this ratio increased slightly with increasing specific ionization loss of the ion Експериментально виміряно електронні виходи вторинної іонно-електронної емісії з нітриду титану на
простріл і на відбиття під час бомбардування α-частинками від радіоізотопного джерела. Показано, що відношення електронних виходів на простріл і на відбиття становить приблизно 1,79, що добре узгоджується з
результатами, отриманими раніше для інших матеріалів і швидких легких іонів. Знайдено, що зазначене відношення помірно зростає зі збільшенням питомих іонізаційних втрат іона. Экспериментально измерены электронные выходы вторичной ионно-электронной эмиссии из нитрида
титана на прострел и на отражение при бомбардировке α-частицами от радиоизотопного источника. Показано, что отношение электронных выходов на прострел и на отражение составляет примерно 1,79, что хорошо
согласуется с результатами, полученными ранее для других материалов и быстрых легких ионов. Найдено,
что указанное отношение слегка возрастает с увеличением удельных ионизационных потерь иона.